Should local public employment services be merged with the local social benefit administrations? - Christian Holzner; Sonja Munz (Center for Economic Studies and ifo Institute (CESifo), 2011)
The German Federal government has allowed some regions (Approved Local Providers) to be solely responsible for the care of long-term unemployed. The remaining regions had to form Joint Local Agencies, where the local social benefit administrations work together with the local public employment services. We find that despite positive self-selection Approved Local Providers do not perform better than Joint Local Agencies. Even more interestingly, using a unique data set on organisational characteristics we are able to show that the organisational features implemented primarily by Approved Local Providers are positively correlated with the job finding probability of the long-term unemployed. Thus, regions that self-selected into Approved Local Providers seem to have implemented a better organisational structure. However, their relatively poor performance overall compared to Joint Local Agencies suggests that they underestimated the benefits of having the local public employment service merged with the local social benefit administration.
Keywords: I38; J64; C31; 330; organisation; labour market integration; evaluation; Arbeitslosenversicherung; Arbeitsvermittlung; Sozialhilfe; Gemeinde; Organisationsstruktur; Wirkungsanalyse; Langzeitarbeitslosigkeit; Berufliche Integration; Beschäftigungseffekt; Deutschland